STUDENTS’ STRATEGIES IN IMPROVING MASTERY OF NEW VOCABULARY IN THE ENGLISH FOR SPECIFIC PURPOSE (ESP) COURSE - Rusmaladewi; Indrawaty Asfah; Andi Kamariah (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This research examines the strategies used by Business English communication students in mastering new vocabulary within the English for Specific Purposes (ESP) course. Using a qualitative research design, data were collected through interviews and questionnaires. The findings indicate that cognitive strategies such as constructing sentences or paragraphs, extensive reading, and watching movies or listening to music help students gain a deeper and more natural understanding of vocabulary usage, thereby strengthening long-term retention. As a result, these strategies are employed by the majority of Business English Communication students to master new vocabulary in the ESP course.Meanwhile, memory strategies, such as mnemonics and flashcards, have proven effective in enhancing short-term memory, enabling students to quickly memorize technical terms. Group discussions, as a social strategy, also have a positive impact by providing an interactive learning environment that enhances contextual understanding and builds confidence in using academic vocabulary.Furthermore, this research highlights that the effectiveness of each strategy depends on its alignment with students' individual needs and learning styles. A well-suited combination of strategies can enrich vocabulary learning experiences in the ESP course, improving memory, comprehension, and the application of vocabulary in professional contexts. Ultimately, these strategies prepare students to succeed in future academic and professional environments.